Spontaneous bilateral posterior capsule rupture in child – case report - Kanigowska, Krystyna; Grałek, Mirosława; Trzebicka, Agnieszka; Chipczyńska, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Isolated posterior capsule rupture without penetrating injury has rarely been reported. Posterior capsule tears can be preexisting, spontaneous or intrasurgical. Authors report a case of progressing bilateral cataract in 3 months old boy, caused by posterior capsule rupture. Rapidly developing cataract with intumescent lens material in vitreous cavity required surgical procedure: pars plana lensectomy and vitrectomy in both eyes.